Ultrasound Improves the Success Rate of a Sural Nerve Block at the Ankle. Issue 1 (1st January 2009) - Redborg, Kirsten E.; Sites, Brian D.; Chinn, Christopher D.; Gallagher, John D.; Ball, Perry A.; Antonakakis, John G.; Beach, Michael L.
Abstract : Background and Objectives: During ankle block performance, anesthetizing the sural nerve is important for generating complete anesthesia of the lateral aspect of the foot. We hypothesized that an ultrasound-guided perivascular approach, utilizing the lesser saphenous vein as a reference, would prove more successful than a conventional approach based on surface landmarks. Methods: Eighteen healthy volunteers were prospectively randomized into this controlled and blinded study. Each subject was placed prone and the right ankle was randomized to receive either an ultrasound-guided perivascular sural nerve block (group US) or a traditional landmark-based sural nerve block (group TRAD). The subject's left ankle then received the alternate approach. The ultrasound technique relied on injecting local anesthetic circumferentially around the lesser saphenous vein. All blocks were performed with 5 mL of 3% chloroprocaine. We evaluated sensory block to ice and pinprick. Secondary outcome variables included performance times, number of needle passes, participant satisfaction, and presence of any complications. Results: At the midfoot position, testing at 10 minutes after block placement revealed a loss of sensation to ice in 94% (complete in 78% and partial in 16%) in the US group versus 56% in the TRAD group (complete in 28%, partial in 28%) ( P <.01). Complete loss of sensation to ice persisted in 33% of the US group as compared with 6% in the TRAD group at 60 minutes ( P <.05). A similar pattern was observed when the blocks were tested with pinprick. Ultrasound-guided blocks took longer to perform on average than the traditional blocks (mean difference of 102 seconds, P <.001). The ultrasound block was subjectively felt to be denser by 88% of the subjects ( P =.001). Conclusions: Ultrasound guidance using the lesser saphenous vein as a reference point results in a more complete and longer lasting sural nerve block than does a traditional approach using surface landmarks.